[Hoath?] College, County of Dublin (1790)
This drawing may possibly be the ruins of Howth Church, County Dublin.
Inscribed in ink on verso of drawing: No. 37.
Title inscribed in ink on verso of drawing.
Watermark l.l. bears the letters "JW" which could be part of the name of the papermarkers "J Whatman".
Formerly held at NLI call number ET 1976 TX 140.
Attributed to Reverend Dr. Wynne, (fl. ca. 1794).
Keywords: Buildings -- Ireland -- Dublin (County) -- 1790-1800.; Ruins -- Ireland -- Dublin (County) -- 1790-1800.; Ink drawings -- Irish -- 1790-1800.; Wash drawings -- Irish -- 1790-1800.